ANALYSIS OF FACTORS INFLUENCE MARRIED WOMEN’S DECISION TO WORK IN BANYUPUTIH VILLAGE, JEPARA REGENCY - Ramadhani, Dita; Prasetyani, Dwi; Sari, Vita Kartika; Patoni, Abdus Sihab (MESP–FEB UNS, 2023)
Gender equality and employment opportunities provide a great opportunity for women to enter the labor market. This study aims to analyze the factors that influence the decision of married women to work in Banyuputih Village, Jepara Regency. Banyuputih village was chosen as a research location because of the existence of a manufacturing industry that was able to boost the village's economy. The number of samples used in the study were 100 respondents in accordance with the objectives of the study. The independent variables used are the level of education, husband's income and the number of children under five. Data analysis was performed using Binary Logistic Regression because the dependent variable was in the form of dummy. The analysis showed that the level of education had a positive and significant effect, while the husband's income variable and the number of children under five had a negative and significant effect on the decision of married women to work in Banyuputih Village.